The children : a novel - Albert, Melissa (William Morrow, an imprint of HarperCollins Publishers, 2026)
"Guinevere Sharpe has two childhoods. In one, she lives in the wooded shadow of her family's isolated Vermont farmhouse; in the other, the pages of her mother's world-famous Ninth City books, where her magical adventures have made her a household name. In reality, Guinevere's childhood isn't the enchanted idyll her mother's readers imagine: she and her older brother are growing up near-feral, unwashed and underfed, escaping each day to the lichen-clotted woods they've made their playland. As Edith Sharpe's books explode into epic popularity, the threats of a rural childhood give way to the escalating perils of fame-until the night it all goes up in flames, leaving Edith's series unfinished and her children the sole survivors. Now an adult coasting on her mother's name, Guinevere is mid-promotion for a ghostwritten memoir when her estranged brother, an artist who has until now spurned his family's legacy, announces an upcoming installation titled Mother. As rumors swirl around a death connected to his last show, unsettling recollections from Guinevere's childhood begin to surface. Her public facade starts to crack, forcing her to confront the questions she's spent the last twenty years running from: What really happened the night of the fire? And what dark history lies behind their mother's creative genius? Wise to the mythic weight childhood memories gather over time, The Children whispers to you from the hallway outside your bedroom, lights flickering as you turn the pages of a book that didn't seem so scary a moment ago. It's a story for anyone who's ever revisited an old favorite and found it cast in a darker light, the line separating magic and memory blurring as the gap widens between the authors we imagined and the people they turn out to be"-- Provided by publisher.